4D printing composite with electrically controlled local deformation. (September 2020) - Shao, Li-Hua; Zhao, Boxuan; Zhang, Quan; Xing, Yufeng; Zhang, Kai
Abstract: 4D printing holds the important potential for various applications in military, robotics, and healthcare. Among the numerous 4D printed materials, the thermally induced shape memory polymer has been the most used one, which is traditional driven by thermal environments like hot water bath or hot stage. In such way, the whole structure deforms at the same time to transform the shape. However, the environment independent local deformation is required for many applications. In this work, the silver nanowires (Ag-NWs) were employed combining with polylactic acid (PLA) to create a novel electrically driven 4D printing composite. Ag-NWs networks ensured the excellent electric conductivity after repeated tensile and bending deformations. As a result, Ag-NWs could be the excellent "heater" to stimulate the local deformation of PLA under an applied voltage. The theoretical constitutive equations were given, which allowed quantitatively design the structure for desired deformation and property. A biomimetic flower with five petals were demonstrated, that each petal could be controlled independently. An application of the 4D printed structure as a gripper grabbing the cargo in the cold icy environment was realized. Our study has great significance for the future application of shape memory composite materials for multi-functionality in different environments. Highlights: Novel 4D printing composite with electrically controlled local deformation was achieved by combining silver nanowires (Ag-NWs) with shape memory polymer. Ag-NWs networks ensured the excellent electric conductivity after repeated deformation. The petals of a 4D printing flower could deform independently. A 4D printing gripper grabbed the cargo in the cold icy environment.